Political and economic governance in the Balkans and Eastern Europe compared - Emerson, Michael (Brussels, 2018)
"The not-yet EU member states of the Balkans and three states of Eastern Europe – Georgia, Moldova and Ukraine – have much in common: geographic proximity to the EU, political priority to become members of the EU, and similar struggles to improve their political and economic governance in line with EU standards and values.